Quercus suber – P. cinnamomi interaction: hypothetical molecular mechanism model - Coelho, A. C. (2012)
Phytophthora cinnamomi Rands is involved in the decline and mortality of Quercus suber L. and Quercus ilex L. in Southern Europe, in particular in Portugal and Spain. The presence and spread of P. cinnamomi in these regions is a severe threat to these oak ecosystems leading to expectable severe consequences for the production of cork and acorns in the near future. Molecular mechanisms underlying oomycete-host interactions are poorly understood. As a first step to identify transcripts involved in the Quercus suber – Phytophthora cinnamomi interaction, we applied complementary deoxyribonucleic acidamplified fragment length polymorphism (cDNA-AFLP) methodology to cork oak seedlings infected with zoospores or mycelium of P. cinnamomi. Forty-four Quercus suber genes that were differentially expressed when exposed to Phytophthora cinnamomi were selected and sequenced. Several of these genes were fully sequenced and the deduced aminoacid sequences showed consistent homology with proteins involved in the defence mechanism of other plant species. These findings led to the design of a simplified hypothetical model that illustrates the initial events of the interaction between Q. suber and P. cinnamomi.